The association between the atherogenic index of plasma and all-cause mortality in patients undergoing peritoneal dialysis: a multicenter cohort study - Yaohua Hu; Liming Yang; Zhanshan Sun; Xiaoxuan Zhang; Xueyan Zhu; Jian Li; Xinyang Li; Mengyuan Yu; Wenpeng Cui (Lipids in Health and Disease)
Abstract Background The Atherogenic Index of Plasma (AIP) has been reported as a strong predictor of all-cause mortality in the overall population. However, the lipid profile changes in individuals with end-stage kidney disease (ESKD) undergoing peritoneal dialysis (PD) may affect the prognostic utility of AIP for all-cause mortality. The connection between them remains unclear. Methods This study included patients receiving PD at five hospitals in China from January 1, 2013, to December 31, 2019, with follow-up until June 30, 2020. The primary exposure variable in this investigation was the logarithm of the triglycerides (TG)/high-density lipoprotein cholesterol (HDL-C) ratio, which was used to compute the AIP, and the outcome variable was all-cause mortality. A Cox proportional hazards regression model was employed to analyze the association between AIP and all-cause mortality. Moreover, stratified analyses were performed to investigate this association further. Kaplan-Meier curves were employed for survival analysis, assessing the prognostic implications of varying AIP levels. Nonlinear associations were examined using smooth curve fitting techniques. Results A total of 869 patients were included in this study, of whom 153 died during the follow-up period. An inverse association was observed between AIP and all-cause mortality risk in the highest tertile compared to the lowest tertile (HR: 0.56, 95% CI: 0.37–0.84) after correcting for potential confounding variables. Moreover, a nonlinear association was observed between the rates of all-cause mortality and AIP. A segmented Cox regression model identified an inflection point at an AIP value of 0.63 (P = 0.014 for the log-likelihood ratio test). More specifically, it was negatively associated with the all-cause mortality risk (HR: 0.42, 95% CI: 0.25–0.73, P = 0.002) when AIP was ≤ 0.63. On the other hand, AIP showed a positive association with the risk of all-cause mortality when it was more than 0.63 (HR: 8.94, 95% CI: 1.66–48.10, P = 0.011). Conclusion The present study identified a non-linear association between AIP and all-cause mortality in patients receiving peritoneal dialysis.